Effects of Ascorbic Acid on Rectal Temperature Fluctuations in Indigenous Turkeys During the Hot-Dry Season - Adenkola, A.Y.; Ayo, J.O. (International Journal of Poultry Science, 2009)
Experiments were performed on 40 indigenous turkeys with the aim of investigating, fluctuations in their rectal temperature (RT) and the effect of ascorbic acid (AA) on during the hot-dry season. Twenty turkeys which served as experimental birds were administered AA orally at the dose of 52 mg kg-1, while the remaining 20 turkeys which served as control were given ordinary water. Measurements of RT were taken for 3 days, one week apart and every hour from 06:00-19:00 h. The results showed that RT values in both experimental and control turkeys significantly (p<0.01) fluctuated with the hours of the day (r = 0.614, 0.612, respectively) and the dry-bulb temperature (r = 0.794, 0.928, respectively). The RT value of 41.2±0.03oC recorded in experimental turkeys was significantly lower (p<0.05) than the corresponding value of 41.5±0.03 °C obtained in control turkeys. The results demonstrated that AA significantly reduced RT values in experimental turkeys. In conclusion, AA administration may be of value in turkeys subjected to unavoidable stressful conditions during the hot-hours of the day.